Antibacterial Action of Citrus Fruits Against Selected Pathogenic Bacteria - Chaturwedi, Shashi Bhushan; KC, Suprabha; Chaudhary, Preety; Chaudhary, Richa; Chaudhary, Richa (Tribhuvan University Journal of Microbiology, 2024)
Objectives: This study's primary goal was to assess citrus fruits' antibacterial effectiveness against particular microorganisms. Methods: The juice and peel of the seven chosen citrus fruits were extracted using a conventional qualitative method in an ethanol solvent. The resulting extracts were then diluted in an aliquot of 1 mL of 10% v/v DMSO. The antimicrobial test was conducted using the Agar well diffusion method. This study was conducted from February and April, 2022. Results: The peel and juice extracts shown varying degrees of inhibitory zones on particular bacteria. Citrus aurantium juice extract was the most efficient citrus fruit extract against Staphylococcus aureus, with a 27mm zone of inhibition, out of the ones that were chosen. On the other hand, a 19mm zone of inhibition was demonstrated by the Citrus reticulata peel extract, which was more efficient against Escherichia coli. Conclusion: Based on the findings, we conclude that citrus fruits may be helpful in preventing bacterial growth because of their strong antibacterial properties.